Studi Literatur: Pelaksanaan Audit Syariah Pada Perbankan Syariah - Azizah Surury, Nurul; Hamdan Ainulyaqin, Muhammad (CV. Lafadz Jaya, 2022)
This study analyzes several things about sharia auditing in sharia banking, including: the concept of supervision, sharia audit framework and governance of Islamic financial institutions; the role of sharia auditors in the Halal Assurance System in Sharia Banks; the role and competence of sharia auditors in supporting sharia banking performance; effectiveness of sharia audit in Indonesia and perspective according to Al-Quran and Hadith; sharia audit challenges; and Islamic bank audits. This research method uses qualitative methods, namely library research by selecting 5 (five) journals and 1 (one) book on sharia auditing. Audits in Islamic banks and conventional banks are very different, so that effective supervision is needed on Islamic banks, in this case a sharia auditor is needed. Sharia auditors have a broader scope, sharia auditors must review sharia compliance to ensure that all operational activities of sharia financial institutions are in accordance with sharia principles. A sharia auditor must also have competence that can be proven through a special certification exam for sharia auditors.